Transformative Metrics: Contributions to the Studies for Monitoring and Evaluating How Science, Technology, and Innovation Can Address Social and Environmental Challenges (2022)
ABSTRACT: This book provides a fresh and comprehensive understanding of the most significant methodological advances in the study of transformative change through policy decision-making; this latter being commonly influenced by metrics and evaluation processes. In this vein, the book presents methodological approaches to the study of sustainable transitions by suggesting that these metrics and evaluation processes can play a new role. It contends that using these approaches in the implementation of policy programmes, projects, and interventions can offer a further reflexive perspective, which helps transformations to take place and enhance metrics’ transformative potential. All in all, this book contributes to the construction of a research agenda that can support necessary changes in our world. The measurement models that are presented here are rooted in transdisciplinary work, reflecting their connection to policy evaluation. In this line, the book compiles reflections about measurement and assessment tools built in situ. These reflections then bring the concepts of transformation and innovation to specific realities, recalibrating methodologies to adapt to new developments and reframe different discussions. Thus, this book does not offer recipes for measuring or evaluating change. Instead, it sparks a discussion regarding several approaches with the potential to increase reflexivity and promote transformative change.